CA‐074Me compound inhibits osteoclastogenesis via suppression of the NFATc1 and c‐FOS signaling pathways. Issue 10 (20th August 2015) - Patel, Neel; Nizami, Saqib; Song, Lee; Mikami, Maya; Hsu, Anny; Hickernell, Thomas; Chandhanayingyong, Chandhanarat; Rho, Shim; Compton, Jocelyn T.; Caldwell, Jon‐Michael; Kaiser, Philip B.; Bai, Hanying; et al.
ABSTRACT The osteoclast is an integral cell of bone resorption. Since osteolytic disorders hinge on the function and dysfunction of the osteoclast, understanding osteoclast biology is fundamental to designing new therapies that curb osteolytic disorders. The identification and study of lysosomal proteases, such as cathepsins, have shed light on mechanisms of bone resorption. For example, Cathepsin K has already been identified as a collagen degradation protease produced by mature osteoclasts with high activity in the acidic osteoclast resorption pits. Delving into the mechanisms of cathepsins and other osteoclast related compounds provides new targets to explore in osteoclast biology. Through our anti‐osteoclastogenic compound screening experiments we encountered a modified version of the Cathepsin B inhibitor CA‐074: the cell membrane‐permeable CA‐074Me (L‐3‐trans‐(Propylcarbamoyl) oxirane‐2‐carbonyl]‐L‐isoleucyl‐L‐proline Methyl Ester). Here we confirm that CA‐074Me inhibits osteoclastogenesis in vivo and in vitro in a dose‐dependent manner. However, Cathepsin B knockout mice exhibited unaltered osteoclastogenesis, suggesting a more complicated mechanism of action than Cathepsin B inhibition. We found that CA‐074Me exerts its osteoclastogenic effect within 24 h of osteoclastogenesis stimulation by suppression of c‐FOS and NFATc1 pathways. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1474–1486, 2015.